Endometriosis: what is new? - Bednarowska-Flisiak, Alicja; Bińkowska, Małgorzata; Dębski, Romuald (Menopause Review/Przegląd Menopauzalny, 2004)
Endometriosis is a quite common disease caused by ectopic endometrium situated outside the uterus. It was described about years ago but it is still not well understood. The common symptoms are pelvic pain, deep dyspareunia and infertility. Endometriosis can occur in almost every organ of the body but the typical sites are different parts of the pelvis: ovaries, anterior and posterior cul-de-sac, uterosacral and broad ligaments. There are many hypotheses as to its etiology. The ectopic endometrium seems to be aggressive, the immunologic milieu of the peritoneal cavity is altered and helps the lesions survive and proliferate. A great number of different growth factors, cytokines and immunomodulators could be found in the peritoneal cavity of affected women. The role of different tissue and serum factors is under research as possible markers of the disease. Pelvic examination during menses is recommended. Transvaginal ultrasonography, MRI, and endometrial and serum markers have the potential to facilitate the diagnosis and can be useful in the follow-up of patients. However, the diagnosis should be confirmed by the histological examination of samples taken during laparoscopy.